Efektivitas Media YouTube sebagai Sumber Belajar dalam Membentuk Kreativitas Siswa pada Mata Pelajaran Seni Budaya dan Prakarya di SD/MI - Evi Fatimatur Rusydiyah; Moh. Rifqi Rahman; Aisya Sava Rahmadila; Amillatuz Zuhriah; Fina Alfiana Damayanti (Institut Agama Islam Negeri (IAIN) Curup, 2023)
In this research, several trials have been carried out related to the subject of cultural arts and crafts through the media of YouTube. The purpose of this research is to find out how students respond when they receive material delivery using two different methods. The first method was carried out in the first class, namely in class 3C, where the delivery of the material used YouTube as an intermediary. Whereas in the second class, namely in the 3D class, the delivery of the material does not use YouTube as an intermediary. This study uses a qualitative approach. The type of research data is qualitative data and the data source is secondary data while the data collection methods used are observation, interviews, and documentation. The results of this study explain that students tend to be more active and enthusiastic in paying attention to the material presented through YouTube media. Whereas in the material presented without using YouTube media, students' responses tended to be less enthusiastic and experienced a little difficulty when practicing the material.